Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition - Erik van Nieukerken; Aleš Laštůvka; Zdeněk Laštůvka (ZooKeys, 2010)
The nine western Palaearctic species of the subgenus Zimmermannia Hering, 1940 and 48 species in the subgenus Ectoedemia Busck, 1907 of the genus Ectoedemia are reviewed. One species in the subgenus Zimmermannia and four species in the subgenus Ectoedemia are described as new: Ectoedemia (Zimmermannia) vivesi A. Laštůvka, Z. Laštůvka & Van Nieukerken sp. n. from southern Spain and Cyprus with unknown host plant, Ectoedemia (E.) hendrikseni A. Laštůvka, Z. Laštůvka & Van Nieukerken sp. n. from southern France on Quercus suber, E. (E.) heckfordi Van Nieukerken, A. Laštůvka & Z. Laštůvka sp. n. from southern England on Quercus petraea and Q. robur, E. (E.) phaeolepis Van Nieukerken, A. Laštůvka & Z. Laštůvka sp. n. from Spain and Portugal probably on Quercus ilex and Q. rotundifolia and E. (E.) coscoja Van Nieukerken, A. Laštůvka & Z. Laštůvka sp. n. from Spain on Quercus coccifera. The following species are redescribed: Ectoedemia (Zimmermannia) hispanica Van Nieukerken, Ectoedemia (Zimmermannia) reichli Z. & A. Laštůvka, 1998, Ectoedemia (E.) algeriensis van Nieukerken, 1985, E. (E.) pseudoilicis Z. & A. Laštůvka, 1998 and E. (E.) alnifoliae van Nieukerken, 1985. Ectoedemia albiformae Puplesis & Diškus, 2003 is synonymised with E. spinosella (Joannis, 1908). Ectoedemia jacutica Puplesis, 1988, previously synonymised with E. agrimoniae (Frey, 1858), is here synonymised with E. spiraeae Gregor & Povolný, 1983. Updated keys to the subgenus Zimmermannia and the Quercus feeding Ectoedemia are provided.